Interannual changes of carbon storage in mangrove forests in Futian based on WorldView-3 remote sensing images - HU Liuliu1, TAN Min2, LUO Qin2, HUANG Zijian2, XIANG Xuelian2, LI Buhang2, YU Shixiao2, WU Zefeng1, YANG Qiong1, HU Ping1* (Guangxi Zhiwu)
Mangroves are unique coastal blue carbon ecosystems in tropical and subtropical areas. However, the dynamic changes of their carbon storage are rarely reported. Based on ground sample points and WorldView-3 high-resolution remote sensing images obtained in 2017, we identified the canopy of dominant mangrove communities in Futian mangrove utilizing random forest algorithm and object-oriented classification methods, and inverted and calculated the area of each dominant community. We then calculated the carbon storage of each dominant community combining the field survey data in 2017, 2020 and 2023, and obtained the spatial distribution and interannual dynamic changes of carbon storage of mangrove communities. The results were as follows:(1)The overall accuracy of the random forest algorithm for canopy identification was 82.29%, with a Kappa coefficient of 0.77; Futian mangrove spaned an area of 93.84 hm2, with Kandelia obovata having the largest distribution area of 49.96 hm2, followed by Avicennia marina, Sonneratia caseolaris, S. apetala, and Bruguiera gymnorhiza, with respective areas of 26.23, 8.90, 6.52, and 0.50 hm2.(2)The total carbon storage of Kandelia obovata community was the highest, followed by Avicennia marina, Sonneratia caseolaris, S. apetala, and Bruguiera gymnorhiza the lowest. The carbon density in Sonneratia apetala and S. caseolaris community showed an increasing trend, and S. apetala community revealed the highest among the five dominant communities. The carbon density of Kandelia obovata community increased first and then decreased, while Avicennia marina community showed a downward trend consistently, and carbon density in Bruguiera gymnorhiza community did not vary significantly. In summary, the carbon storage of mangrove dominant communities in Futian did not change much from 2017 to 2023. The carbon sequestration capacity of mangrove in Kandelia obovata, Sonneratia apetala and S. caseolaris communities was stronger. The carbon density of Avicennia marina community decreased year by year, while that of Bruguiera gymnorhiza community was relatively stable. These results provide foundational data for evaluating the carbon sequestration capacities of different dominant communities in Futian mangrove, in tandem with scientific support for subsequent mangrove restoration and management.